2015
DOI: 10.3109/08037051.2014.1000562
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hypertension on retinal nerve fiber layer thickness and its association with carotid intima media thickness

Abstract: RNFL thickness is reduced in hypertensive patients and may be associated with atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Previous studies reported contradictory results on the impact of hypertension and blood pressure on pRNFLT 9,23,24 . Our results show reduced pRNFLT in hypertensive patients, but no association of pRNFLT with actual systolic blood pressure.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies reported contradictory results on the impact of hypertension and blood pressure on pRNFLT 9,23,24 . Our results show reduced pRNFLT in hypertensive patients, but no association of pRNFLT with actual systolic blood pressure.…”
Section: Discussionmentioning
confidence: 94%
“…However, in our study population, age and a history of systemic hypertension generally predicted a considerable decrease in pRNFL thickness. Atherosclerosis in the setting of systemic hypertension appears to be associated with pRNFL thinning [ 21 ]. In addition, the relationship between aging and pRNFL thinning appears robust despite the presence of several confounders.…”
Section: Discussionmentioning
confidence: 99%
“…It provides up to 9 sector measurements rather than average thickness alone for different layers. To date, there are few reports of evaluation of macular thickness and RNFL in patients with systemic sHT (10, 11). All of these reports included the patients with sHT who were receiving antihypertensive medication.…”
Section: Introductionmentioning
confidence: 99%